Facilitators, barriers, and recommendations related to the informed consent of Marshallese in a randomized control trial. (June 2020) - Purvis, Rachel S; Eisenberg, Leah R; Trudeau, Christopher R; Long, Christopher R; McElfish, Pearl A
Background: The Pacific Islander population is the second fasting growing population in the United States and Arkansas is home to the largest Marshallese population in the continental US. The Marshallese community have significant health disparities with high prevalence of diabetes, heart disease, and obesity compared to the general US population. Using a community-based participatory research approach, researchers and Marshallese community stakeholders identified diabetes as the top health issue for research. Methods: From 2014 to 2018, a randomized control trial was conducted comparing standard diabetes management education with a culturally adapted family model of standard diabetes management education delivered in participants' homes by Marshallese community health workers and certified diabetes educators. Interviews were held with Marshallese participants to document their experiences with and perceptions of the informed consent process for this randomized control trial. Results: Participants provided feedback on the process of enrolling in the study, describing barriers and facilitators to giving informed consent from their perspective, and offering recommendations for improving the informed consent process. Conclusion: Findings suggest that informed consent with underserved communities, including immigrant and migrant populations who do not speak English or have limited English proficiency, is possible, and that using a community-based participatory research approach can help facilitate the informed consent process.